PEMANFAATAN RUMPUT AIR (Hydrilla verticillata) SEBAGAI KOMPOS PADA TANAMAN BUNGA KOL (Brassica oleracea) - Raudatul Dahliana Safitri; Agung Nugroho; Yuspihana Fitrial; Fatmawati Fatmawati (EnviroScienteae, 2019)
The purpose of this study was to obtain quality and standards for water grass (H. verticillata) as an alternative raw material for the production of compost fertilizer on cauliflower plants (Brassica oleracea var botrytis L.). The method used in this study used a completely randomized design (CRD), a single factor with analysis of data using ANOVA with a Real Difference (BNT) test. At Po (control) 100% land, P1 100% water grass, 50% P2 grass water + 50% cow manure and 25% P3 water grass + 75% cow manure. The optimal research results on the growth of cauliflower with a ratio of 50% water grass + 50% cow manure with a flower mass parameter of 396g ± 31, plant mass 563 ± 37, root mass 45.31 ± 2 and% NPK content, N 0.99 %, P 0.53%, K 0.32%.